Proposal of a Hybrid LoRa Mesh / LoRaWAN Network - Almeida, Nelson C. [UNESP]; Rolle, Rodrigo P. [UNESP]; Godoy, Eduardo P. [UNESP]; Ferrari, Paolo; Sisinni, Emiliano (Institute of Electrical and Electronics Engineers (IEEE), 2020)
There is a recent interest in the deployment of Low Power Wide Area Networks (LPWANs), such as LoRaWAN, to support Internet of Things (IoT) applications. Even though the main advantage of these LPWANs are the long rage communication, the challenge of providing seamless and shadow area coverage still remains. This paper presents a proposal of a hybrid LoRa Mesh/LoRaWAN network to cope with this challenge. In this proposal, a mesh network of LoRa nodes are connected to a Proxy node that works as a mesh coordinator and is also connected to the LoRaWAN network. The advantage of this topology is the improvement of the communication coverage in shadow areas where a regular LoRaWAN node cannot be reachable in cases of obstacles or topography. The development of the LoRa Mesh network as well as the routing mechanism are presented and verified with experimental results. Finally, the integration of the LoRa Mesh with the LoRaWAN networks is discussed and a proposal is presented.
Keywords: AODV protocol; Industry 4.0; Internet of Things; LoRa